Proceso de servicios y su impacto en la rentabilidad económica en la compañía de transportes pesados JAOP S.A. 2021. - Jacome Paredes, Vanessa Paola (2022)
The project called “Service process and its impact on economic profitability in the Compañía de Transportes Pesados JAOP S.A. 2021” developed in the Valencia canton has as general objective Analyze the service process and its impact on the economic profitability of the Compañía de Transportes Pesados JAOP S.A. The research problem posed reflects that the company lacks service process flowcharts as well as the existence of the application of profitability indicators, this is due to the fact that the organization has recently been operating in the commercial market, therefore it is developing improvements such as also the implementation of strategies that provide a competitive advantage. As part of the development of the investigation, the logical historical method, the analytical method, the inductivedeductive method were applied. The types of research used were bibliographic, field and descriptive research. The research technique used was the census and the interview and the instrument used was the questionnaire. The population consisted of 18 people being grouped by partners, driver and administrative staff, to whom the application of the research instruments (interview and survey) was developed. The results of the investigation indicate the application of the calculation of the profitability ratios, where it was shown that the ROA is 0.90% while the ROE is 1.36 dollars following the value of 1.11 dollars that corresponds to the gross profit of the company. . As can be seen, the company has no obligations to third parties, which makes it more solvent and at the same time invulnerable. The proposed proposal is constituted by the identification of the service process, followed by the creation and design of process flowcharts that help the company to meet the objectives and finally the implementation of an operational plan to be carried out. The conclusions and recommendations refer to the purpose of developing an implementation guide as a practical basis for further development of the company’s service process, quickly adjusting to the strategies and processes that I develop.